2013
DOI: 10.1186/2193-1801-2-370
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic analysis and FPGA implementation of SHE controlled three phase CHB 11-level inverter in MV drives using deterministic and stochastic optimization techniques

Abstract: With the advancements in semiconductor technology, high power medium voltage (MV) Drives are extensively used in numerous industrial applications. Challenging technical requirements of MV Drives is to control multilevel inverter (MLI) with less Total harmonic distortion (%THD) which satisfies IEEE standard 519-1992 harmonic guidelines and less switching losses. Among all modulation control strategies for MLI, Selective harmonic elimination (SHE) technique is one of the traditionally preferred modulation contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…It was found that BFA consistently outperformed PSO under all test systems and configurations. It can be observed that BFA converges to a better solution in a faster time (Vesapogul et al, 2013). This trend was consistently observed with all problems attempted.…”
Section: Comparison With Particle Swarm Optimisation (Pso)supporting
confidence: 65%
“…It was found that BFA consistently outperformed PSO under all test systems and configurations. It can be observed that BFA converges to a better solution in a faster time (Vesapogul et al, 2013). This trend was consistently observed with all problems attempted.…”
Section: Comparison With Particle Swarm Optimisation (Pso)supporting
confidence: 65%
“…Usually, this is done offline, using optimization techniques such as the Newton-Raphson (NR) method [14]- [17]. More complex techniques such as the genetic algorithm (GA) [15], [18]- [20] and the particle swarm optimization (PSO) [15], [21], [22] have also been demonstrated. Although these new techniques are fast in determining the optimized angle, the solutions only minimize the harmonics rather than eliminate them.…”
Section: Introductionmentioning
confidence: 99%
“…Since the effectiveness of the SHE method depends heavily on the switching angle, various algorithms have been developed for determining the optimum switching angles [14], [15]. Usually, this is done offline, using optimization techniques such as the Newton-Raphson (NR) method [14]- [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these equations increase, solving them becomes a challenge. One of the most widely used techniques is the Newton-Raphson (NR) method [17], [18]. This is an iterative method to find complex roots in polynomials and roots of equations with several variables.…”
Section: Introductionmentioning
confidence: 99%